(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Hepatitis a Virus Is a Very Common Infection In The Pediatric Age Group, Especially in Developing Countries and Pleural Effusion Is One of It Rare Extra-Hepatic Complication. Here We Are Reporting a Case of Acute Hepatitis a Infection, Complicated With Pleural Effusion. JCMCTA 2016 ; 27 (1) : 72 - 74